Characterisation and classification of soils in the dry sub-humid area of Maiduguri, Borno state, Nigeria - Talha, I. Z; Buji, I. B.; Adamu, I. (ADAN JOURNAL OF AGRICULTURE, 2025)
This study examines the characteristics and classification of soils in a dry, sub-humid area of Borno, North- Eastern Nigeria. The objective was to provide detailed soil information for improving land use, research, and agricultural productivity. It involved soil sampling from eight pedons representing upland, midland, and lowland areas. We examined soil samples for their morphological, physical, and chemical characteristics. The soils were classified using the taxonomic and the world reference base systems. Pedon 8 has a very high organic carbon content, exceeding 2.0%, in both its surface and subsurface horizons. Pedon 1 shows high organic carbon only in the surface Ap horizon, while all other pedons are rated low on both surfaces and suboptimal for sustainable productivity. Nitrogen values for crop production were adequate in the surface and subsurface of pedons 7 and 8, ranging from 0.2 to 0.5%. The Ap horizons of Pedons 1, 4, 6, and 8 have medium levels of available phosphorus, which can support crops with some inputs. In contrast, other pedons exhibit low phosphorus levels (5 to 10 mg/kg), indicating a likely deficiency. The pH values (6.20 to 6.81) are neutral to slightly acidic in all soils studied. Cation exchange capacity (15.15 to 34.22 cmol/kg) and base saturation of over 97% in the Ap surface horizons are often high, indicative of nutrients present. The nutrient availability decreases with depth in organic carbon, total nitrogen, and available phosphorus diminish in the subsurface horizons. Pedons 1 - 8 are Typic Haplustept (USDA soil taxonomy) while correlating with the Eutric Cambisols of the WRB system for soil resources. Thus, it needs specialised moisture and nutrient management. These findings will inform future land management and farming practices for optimised soil use in the region.